(DIS)FIGURING WHITE TEMPLATE VISION THROUGH PASSIONE: UN’AVVENTURA MUSICALE. - Stefania Capogreco (Nepan editor, 2017)
This paper suggests disrupting north-normative thought in Italian Studies by recovering the various Souths haunting and inhabiting white template vision. I do this by disclosing the fleshy folds of John Turturro’s complex audio-visual work Passione: Un’Avventura Musicale (2010), which draws on a broad assemblage of Neapolitan music and theatricalities. Having previously navigated away from Guillaume Bernardi’s reading of Passione’s sixteen linear sequences (2015; CAPOGRECO & MESSINA, 2016), I rhizomatically pieced together (MARKS, 2000) non-linear sequences of sotto/terrone’dvisionaround motifs of “the Sea” and “dirtied mirrors”. Here I articulate how Passione’s “fucked ones” who dare to hold up a mirror to their own dirtied reflections (ANZALDÚA, 1987, p. 10) function as “out of focus maps” disorienting the (caucacentric, male) template body (PUGLIESE, 2005). Further, I re-envision Passione’s “James Senese Sequence” (BERNARDI, 2015, p. 120) as sotto/terrone’dclimax of “racial bits” haunting Italian/North American templates.